국가 특성이 창업활동에 미치는 영향 실증 분석 - 김형준(Hyung Jun Kim); 민태기(Tae Ki Min); 왕정복(Jingbu Wang); 디아나쉴러(Diana Schuler); 오근엽(Keun Yeob Oh) (벤처창업연구, 2020)
The purpose of this study is to empirically analyze the factors that affect start-up activities at the national level. Unlike most existing research about entrepreneurship at the individual level, this empirical analysis makes use of the total early-stage entrepreneurial activity(TEA) index at national level. This was developed by the Global Entrepreneur Monitor (GEM) as the measure for the degree of entrepreneurship of the countries. Based on the previous studies, not only national income level and unemployment rate, but also other factors including the cultural characteristics of the countries were included in our regression model. Using GEM's panel data, we found that the effectiveness of the factors depends on the stage of economic development. In particular, we found 'U-shape' relationship between the level of per capita income and entrepreneurship activity by the panel regression analysis using quadratic function. This analysis result can explicitly confirm what the existing literature have explained descriptively. Furthermore, the governmental support programs are shown to have significantly positive effects on the entrepreneurship or start-up activities in the factor-driven and efficiency-driven economies. On the contrary, those programs were not very helpful in the innovative economies. Lastly, this research suggests that the 'education and training' and the 'entrepreneurial culture' be the supportive norm for new business regardless of the economic development level. 본 연구는 국가 경제 성장과 관련된 창업 (start-up) 활동에 영향을 미치는 요인을 분석하는 국가 수준에서의 실증 연구이다. 창업 활동의 기반인 기업가정신에 대한 개인 수준에서 분석과 달리 GEM (Global Entrepreneur Monitor)에서 발행한 연간 데이터베이스를 활용한 실증 분석을 수행하였다. 나라별 초기창업활동 (TEA: total early-stage entrepreneurial activity) 지수를 이용하여 TEA에 영향을 미치는 영향요인을 경제 요인과 비경제적 요인을 구분하여 분석하였다. 선행 연구를 기반으로 국민소득 수준, 실업률을 포함하여 국가의 문화적 특성 변수 등 9개 요인을 국가 창업 활동의 영향 요인으로 제시하였으며 경제발전 수준에 따라 요소주도형, 효율주도형, 혁신주도형으로 국가를 구분한 패널데이터를 회귀 분석 모형을 통하여 실증 분석하였다. 본 연구의 분석 결과, 기존연구들에서 설명하고 있는 국민소득 수준과 창업 활동 사이의 U자 형태'를 명시적인 2차 함수 회귀분석을 통하여 추정하였으며 그에 따라 창업활동의 변곡점이 되는 소득수준을 발견하였다. 이러한 결과를 통해서 요소주도형 및 효율성주도형 경제에서는 생계형 창업활동이 활발한 반면 혁신주도형 경제에서는 기회추구형 창업활동이 활발하다는 기존의 주장들을 설명할 수 있음을 보였다. 특히, 창업활동 활성화를 위한 정부지원 프로그램에 대해 실증분석해 본 결과, 요소주도형 및 효율성주도형 경제에서는 유의한 긍정적 효과를 미치고 있으나 혁신형 경제에서는 그 효과가 오히려 부정적이라는 결과를 발견하였다. 이는 창업지원 정책이 경제발전단계에 따라 달라져야 함을 보여주는 결과로서 많은 정책적 시사점을 제시한다. 마지막으로 창업관련 교육의 정도와 새로운 비즈니스를 지원하는 사회문화적인 규범으로서의 창업 문화는 국가의 경제 수준과 상관없이 모두 창업활동에 긍정적인 영향을 미치고 있음을 발견하였다. 이는 어느 단계의 경제이든 창업 문화 조성이 필요하다는 시사점을 함축하고 있다.